THE EFFECT OF ASTAXANTHIN ON TUMOR NECROSIS FACTOR ALPHA (TNF-α) AND INTERLEUKIN 10 (IL-10) EXPRESSION IN UV-B-INDUCED RATS MODEL - Rahman, Akhmad Setyo; Budhy, Theresia Indah; Nugraha, Jusak; Fadhilah, Nur Lailatul (Folia Medica Indonesiana, 2025)
The skin, the largest organ in the human body, serves as a protective barrier against external factors. Exposure to UV-B radiation accounts for approximately 90% of skin damage, leading to aging characterized by dryness and wrinkles. Proper nutrition has been associated with skin repair and delayed aging. Astaxanthin, known for its pharmacological properties including anti-cancer, anti-diabetic, anti-inflammatory, and antioxidant activities has garnered attention for its ability to improve damaged skin when administered as a daily supplement. This study investigated the roles of TNF-α and IL-10 as inflammatory markers in skin damage and repair, which remain underexplored. A true experimental randomized posttest-only control group design was employed using 24 male white rats divided into four groups: (1) normal group (N), untreated rats; (2) control group (C), rats administered with olive oil (5 ml/kg BW); (3) treatment group 1 (P1), rats exposed to UV-B and administered with olive oil (5 ml/kg BW); and (4) treatment group 2 (P2), rats exposed to UV-B and administered with astaxanthin (10 mg/kg BW) combined with olive oil (5 ml/kg BW). ANOVA and Games-Howell post-hoc tests revealed significant differences (p < 0.05) among groups, except between the control (C) and normal (N) groups. Astaxanthin (10 mg/kg BW) demonstrated both curative and protective effects by reducing TNF-α expression (pro-inflammatory) and increasing IL-10 expression (anti-inflammatory) in UV-B-induced rats. These findings highlight astaxanthin’s potential as a therapeutic agent for UV-B-induced skin damage.